2019
DOI: 10.1002/srin.201900213
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Analysis of Purging Plugs by Applying Fluid–Solid Conjugate Heat Transfer Modeling

Abstract: Purging plugs are important functional units in advanced steel‐making processes, which experience extreme heat exchange and temperature changes during the purging procedure. Fluid–solid conjugate heat transfer modeling is conducted to determine the inconstant and instantaneous heat transfer coefficients at slit walls. Further thermomechanical simulations are performed on the purging plug by assuming elastic material behavior. Dimensionless temperature change and stress analysis indicate that transverse tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…Figure also shows that the difference in the mixing time for different slit diameters is insignificant when the gas flow rate is larger than 3.01 NL min −1 ; this trend agrees well with the previous research . This is likely due to the consumption of the stirring energy, which prolonged the mixing time …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure also shows that the difference in the mixing time for different slit diameters is insignificant when the gas flow rate is larger than 3.01 NL min −1 ; this trend agrees well with the previous research . This is likely due to the consumption of the stirring energy, which prolonged the mixing time …”
Section: Resultssupporting
confidence: 91%
“…Recently, the model developed by Tan et al shows that the stress concentration of purging plug with rectangular slits is directly related to its failure in service, whereas the stress concentration of purging plug with circular slits was alleviated significantly . However, a comprehensive understanding of the metallurgical effect of this type of purging plug is still required for effective process control and possible process optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Under the periodic thermal load, the spalling of layers from the hot face occurs. Referring to the previous research, 23) it can be found that this displacement position of purging plug with rectangular slits is agreed with the practical fracture phenomena that also was considered as spalling well. Comparing with purging plug with rectangular, the spalling of purging plug with circular slits is lesser in industry.…”
Section: Thermomechanical Resultssupporting
confidence: 85%
“…22) The geometry of the purging plug with rectangular slits can be found in our previous literature. 23) Due to the geometrical symmetry, only one-tenth of the actual purging plug with circular slits was established for conducting the numerical simulation, as shown in Fig. 2.…”
Section: Geometrymentioning
confidence: 99%
See 1 more Smart Citation